THE MEDAN COMMUNICATIONS AND INFORMATICS AGENCY'S COMMUNICATION STRATEGY USING INSTAGRAM TO INCREASE MEDIA LITERACY IN MEDAN - Rashin Salsabila; Irma Yusriani Simamora (RADJA PUBLIKA, 2026)
The rapid development of social media has made it easier for the public to access and distribute information, but it has also increased the risks of hoaxes and inaccurate assessments of digital information. This study aims to analyze the communication strategy implemented by the Medan City Communication and Information Agency through the Instagram account @diskominfomedan to improve media literacy among the people of Medan City. The study employed a qualitative approach with a descriptive method. Data were collected through in-depth interviews, observation of account activities and content, and documentation. Informants were selected purposefully based on their involvement in account management and information reception, while credibility data was examined through source and technique triangulation. The findings show that the communication strategy was implemented by appointing credible communicators, identifying diverse target groups, developing informative, educational, and persuasive messages, and using the visual and interactive features of Instagram. Content concerning hoax prevention, responsible social media use, public information, and positive content production encouraged informants to become more critical, selective, cautious, and responsible in receiving and sharing digital information. The study concludes that alignment among communicators, audience characteristics, message quality, media selection, and effect evaluation makes Instagram an effective government communication channel for supporting public media literacy in Medan City.